2021
DOI: 10.3390/ijerph18168601
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Intention of Visiting Urban Green Spaces after the COVID-19 Lockdown in China

Abstract: This study addresses students’ perceptions of using urban green spaces (UGSs) after the easing of COVID-19 lockdown in China. We questioned whether they are still mindful of the risks from the outdoor gathering, or conversely, starting to learn the restoration benefits from the green spaces. Online self-reported surveys were distributed to the Chinese students aging from 14 to 30 who study in Hunan and Jiangsu Provinces, China. We finally obtained 608 complete and valid questionnaire forms from all participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Seeing someone go on a trip and post it on social media influenced me to travel [34] Intention to Travel INT1 I want to go traveling as soon as possible [25] INT2 I intended to travel for leisure [25] INT3 I am tempted to travel after seeing several travel promotion videos on social media [34] INT4 I am thinking of spending time with a different vibe somewhere [32] INT5 I would like to try and do something new for a short break [29] Following the theoretical framework, the questionnaire was formulated to analyze the factors that affect visiting behavior in Bali during the COVID-19 pandemic in Indonesia. The questionnaire consisted of two parts.…”
Section: Smi4mentioning
confidence: 99%
“…Seeing someone go on a trip and post it on social media influenced me to travel [34] Intention to Travel INT1 I want to go traveling as soon as possible [25] INT2 I intended to travel for leisure [25] INT3 I am tempted to travel after seeing several travel promotion videos on social media [34] INT4 I am thinking of spending time with a different vibe somewhere [32] INT5 I would like to try and do something new for a short break [29] Following the theoretical framework, the questionnaire was formulated to analyze the factors that affect visiting behavior in Bali during the COVID-19 pandemic in Indonesia. The questionnaire consisted of two parts.…”
Section: Smi4mentioning
confidence: 99%
“…Even visual contact with natural elements was found to be beneficial for their mood [186,187]. As an outcome, the appreciation and value of GSs also increased in students' perceptions [188][189][190][191]. Along the same lines, part-time and full-time employees had higher scores on the ROS scale.…”
Section: Discussionmentioning
confidence: 86%
“…Literature studies on the COVID-19 pandemic revealed that natural deprivation associated with lockdown leads to restriction of physical activity and experience of negative emotions such as anxiety and depression among university students ( 27 , 35 ). On the contrary, exposure to the natural environment during COVID-19 helps enhance an individual's perception of nature and reduces negative emotions such as anger, fear, and confusion ( 36 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It also has been demonstrated that, as a basis for the restorative effects of the environment, preferences moderate the effect of perceptions of green space on positive emotion ( 56 ). After experiencing the COVID-19 lockdown, university students were more eager to be in outdoor environments ( 35 , 57 ). The positive attitude toward being outside may have an impact on students' perceived naturalness and landscape preference, which may affect their positive emotions about enjoying the CGSs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%